Leucoagaricus gujratensis sp. nov. (Agaricaceae, Agaricales) from Pakistan - Rehman, Amatu; Usman, Muhammad; Afshan, Najam Ul Sehar; Khalid, Abdul Nasir (Phytotaxa, 2023)
A novel mushroom, occurring on sandy soil was collected from scrubland of Gujrat district, Pakistan. Phylogenetic analyses of the nrDNA ITS region revealed that it clusters within Leucoagaricus section Leucoagaricus. Further morpho-anatomical analyses confirmed its uniqueness, and it is here described as Leucoagaricus gujratensis sp. nov. The distinguishing characters of this novel taxon are fragile basidiomata with brown to light brown squamules in the center on milky white pileus surface; creamy stipe with white central annulus; lacrymoid to amygdaliform basidiospores (5.4–8.6 × 3.9–5.5 μm) and clavate to slightly fusiform and fabiform cheilocystidia. The new mushroom resembles La. candidus in appearance but the morpho-anatomical and molecular characters prove its novelty. The number of Leucoagaricus species in Pakistan has reached up to 14.